Unconventional nuclear weapons. - Zorpette, G.
Of the countless scenarios of terrorist mayhem, none quickens the pulse quite like the menace of a nuclear bomb. In light of the low-tech but catastrophic attacks on the World Trade Centre, building a nuclear bomb suddenly seems an unnecessarily difficult and risky proposition. Why build a bomb when there are far cheaper and simpler ways of waging nuclear terror? Analysts have accordingly turned their attention to two other possibilities that, for all their comparative simplicity, would deliver much of the bang of a bomb. Flying a fully fueled jumbo jet into a nuclear reactor is one. The other is using radioactive nuclear materials to kill or sicken people or render tracts of land uninhabitable by, for example, scattering the materials with a conventional explosion. This paper briefly discusses the likelihood of these two types of terrorist attack and the need to protect nuclear power stations and spent fuel from theft by terrorists
Keywords: Direct attack on nuclear reactor; Fueled jumbo jet; Nuclear power stations protection; Nuclear terror; Radioactive nuclear materials; Radiological dispersion devices; Spent fuel protection; Terrorism; Unconventional nuclear weapons